Systematic evaluation and re-evaluation of buyang huanwu decoction in treating ischemic stroke - Da-yuan Zhong; Lan Li; Ruo-meng Ma; Yi-hui Deng (Elsevier, 2022)
Background: The Buyang Huanwu Decoction (BYHWD) originated from Wang Qingren's "Yi Lin Gai Cuo". It has the effect of tonifying qi and activating blood circulation and dredging collaterals which is recommended for the treatment of Ischemic stroke in China. In recent years, there have been many systematic reviews of Ischemic stroke treated by BYHWD assessing the efficacy of BYHWD in the treatment of Ischemic stroke in the acute, convalescent and sequelae stages. Because of the different methods of analysis, the quality and quality of the evidence obtained in these systematic reviews is different, so a systematic re-evaluation was needed to comprehensively evaluate the strength of these studies. Methods: Systematic reviews and meta-analyses of Ischemic stroke treated by BYHWD were identified through the Web of Science, PubMed, CNKI, Weipu, and Wanfang databases. The included studies were selected for literature screening, methodological quality evaluation, and evidence level evaluation by two investigators. The methodological quality was evaluated by the 2020 PRISMA guidelines, Assessing the Methodological Quality of Systematic Reviews (AMSTAR) scale, and the evidence quality was evaluated by the GRADE criteria. Results: Overall, 12 studies involving 28,594 patients between 2006-2021 were included in this analysis. The methodological quality evaluation based on 2020 PRISMA guidelines results showed that there were many weaknesses in registration and protocol, support, competing interests, competing interests and availability of data, code and other materials. The AMSTAR scale evaluation results showed that the 12 studies were very low quality. The results of the GRADE criteria evaluation showed that the quality of the evidence was scattered, with mainly low-quality evidence. Conclusion: The methodological quality of systematic reviews and meta-analyses of BYHWD in treating Ischemic stroke was generally poor, and the quality of evidence was generally low.